Use of Giardia, which appears to have a single nucleotide-sugar transporter for UDP-GlcNAc, to identify the UDP-Glc transporter of Entamoeba - Banerjee, Sulagna (Mol Biochem Parasitol, 2008)
Nucleotide-sugar transporters (NSTs) transport activated sugars (e.g. UDP-GlcNAc) from the cytosol to the lumen of the endoplasmic reticulum or Golgi apparatus where they are used to make glycoproteins and glycolipids. UDP-Glc is an important component of the N-glycan-dependent quality control (QC) system for protein folding. Because Entamoeba has this QC system while Giardia does not, we hypothesized that transfected Giardia might be used to identify the UDP-Glc transporter of Entamoeba. Here we show Giardia membranes transport UDP-GlcNAc and have apyrases, which hydrolyze nucleoside-diphosphates to make the antiporter nucleoside-monophosphate. The only NST of Giardia (GlNst), which we could identify, transports UDP-GlcNAc in transfected Saccharomyces and is present in perinuclear and peripheral vesicles and increases in expression during encystation. Entamoeba membranes transport three nucleotide-sugars (UDP-Gal, UDP-GlcNAc, and UDP-Glc), and Entamoeba has three NSTs, one of which has been shown previously to transport UDP-Gal (EhNst1). Here we show recombinant EhNst2 transports UDP-Glc in transfected Giardia, while recombinant EhNst3 transports UDP-GlcNAc in transfected Saccharomyces. In summary, all three NSTs of Entamoeba and the single NST of Giardia have been molecularly characterized, and transfected Giardia provide a new system for testing heterologous UDP-Glc transporters.